2000
DOI: 10.1021/ic9908975
|View full text |Cite
|
Sign up to set email alerts
|

Monochlorogallane:  Physical Properties and Structure of the Gaseous Molecule H2Ga(μ-Cl)2GaH2 As Determined by Vibrational, Electron Diffraction, and ab Initio Studies

Abstract: Monochlorogallane, synthesized by the metathesis of gallium(III) chloride with an excess of trimethylsilane at ca. 250 K, has been characterized by chemical analysis, by its IR, Raman, and 1H NMR spectra, and by the products of its reaction with trimethylamine. The vibrational spectra of the vapor species isolated in solid Ar, N2, or CH4 matrixes at ca. 12 K imply the presence of only one species, viz. the dimer with an equilibrium structure conforming to D2h symmetry. The structure of this molecule has been d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 46 publications
(86 reference statements)
2
30
0
Order By: Relevance
“…The crystal structure (Figure 1) showed some residual electron density close to the gallium center in the approximate region where hydride substituents would be expected. However, the failure to detect a gallium hydride signal in the 1 H NMR spectrum or an absorption around 2000 cm −1 (ν Ga−H ) in the IR spectrum, 19 followed by the detection of a signal in the 71 Ga NMR spectrum at −703 ppm, which is in the typical region for gallium(I) compounds, 2 convinced us that we had indeed isolated a gallium(I) species. As this finding was supported by preliminary DFT calculations, which indicated that the Hydrosilanes have long been known to convert chlorogallanes into hydrogallanes at or below room temperature, as according to eq 2.…”
Section: Gaclmentioning
confidence: 80%
See 3 more Smart Citations
“…The crystal structure (Figure 1) showed some residual electron density close to the gallium center in the approximate region where hydride substituents would be expected. However, the failure to detect a gallium hydride signal in the 1 H NMR spectrum or an absorption around 2000 cm −1 (ν Ga−H ) in the IR spectrum, 19 followed by the detection of a signal in the 71 Ga NMR spectrum at −703 ppm, which is in the typical region for gallium(I) compounds, 2 convinced us that we had indeed isolated a gallium(I) species. As this finding was supported by preliminary DFT calculations, which indicated that the Hydrosilanes have long been known to convert chlorogallanes into hydrogallanes at or below room temperature, as according to eq 2.…”
Section: Gaclmentioning
confidence: 80%
“…The corresponding data for (H 2 GaCl) 2 are 5.46 ppm and 2021 cm −1 . 19 Solutions of compound 4 in C 6 D 6 slowly eliminate H 2 at room temperature, and after several hours the 71 Ga NMR spectrum shows a weak peak at −645 ppm (w 1/2 = 1100 Hz), indicating the presence of Ga(I) in an asymmetric environment. A microcrystalline solid of a compound tentatively identified as GaN(SO 2 CF 3 ) 2 , 5, was obtained after leaving a hexane/C 6 D 6 solution of 4 standing at room temperature for 4 weeks.…”
Section: Gaclmentioning
confidence: 99%
See 2 more Smart Citations
“…The University of York GED instrument was formerly housed at the University of Reading and was initially commissioned in the late 1960s. During the 1990s and into the first decade of the new millennium, Aarset, Rice, and Page oversaw a particularly prolific period of operation in which many gas-phase structures of organometallics and small organic and main-group molecules were characterized using the instrument, and collaborative work was carried out with other electron diffractionists including Rankin and Hedberg . The instrument was acquired by the University of York in 2015, and this article details the recommissioning of the instrument and describes the contemporary GED experiment.…”
Section: Introductionmentioning
confidence: 99%